PENYULUHAN POLA ASUH ORANGTUA DALAM MENINGKATKAN PENGELOLAAN EMOSI PENCEGAHAN STUNTING DI DESA SETIAJAYA - Apriyanty, Henny; Yuniarti, Tatik; Fakhran Al Ramadhan, Muhammad (Universitas Islam 45 Bekasi, 2023)
Parenting is one of the factors that cause stunting. Parenting has an important influence on the growth and development of a child. What's more, when it comes to babysitting, psychological conditions that have great influence are emotions because parents who don't have good emotional management will have harder behavior, less sensitive to children, quickly feel angry and even depressed. Therefore, a good parenting must be side by side with good management as well. Respondents in this program are parents of grade 6 students. The implementation method uses observation and interview with the principal of Setiajaya Village to find out the problems that occur, then counseling to provide additional knowledge to parents of students related to parenting patterns, and management of emotions and relaxation techniques roleplay. In this implementation, results are obtained, namely the increasing audience's knowledge of proper care to be given to their children, children's nutritional needs, children's growth and development, such as parenting patterns and how to handle emotions well. In addition, audience skills are increasing to manage emotions by using relaxation techniques that can be done at home.